2019
DOI: 10.1016/j.engstruct.2019.01.054
|View full text |Cite
|
Sign up to set email alerts
|

A full-scale timbrel cross vault subjected to vertical cyclical displacements in one of its supports

Abstract: Up-and-down cyclical displacement of supports-foundations, due for example to the presence of expansive soils, can affect the integrity of a structure and may even lead to its collapse. A recent study carried out at the ICITECH laboratories of the Universitat Politècnica de València analysed the effects of earth settlements on the behaviour of masonry cross vaults. One of the tests involved the construction and testing of a full-scale timbrel cross vault, one of whose supports was subjected to up-and-down vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 20 publications
1
15
0
5
Order By: Relevance
“…An interesting fact that is noted is that the crack pattern should be much diffused also in the extrados, although unfortunately, no documentation is available in the present. The cracks simulated in the extrados find confirmation also in experimental studies of masonry cross vaults (Torres et al, 2019).…”
Section: Observed Damage and Structural Assesment Of Masonry Vautlssupporting
confidence: 70%
See 1 more Smart Citation
“…An interesting fact that is noted is that the crack pattern should be much diffused also in the extrados, although unfortunately, no documentation is available in the present. The cracks simulated in the extrados find confirmation also in experimental studies of masonry cross vaults (Torres et al, 2019).…”
Section: Observed Damage and Structural Assesment Of Masonry Vautlssupporting
confidence: 70%
“…Further understanding of the structural behaviour could be developed through experimental investigating. Torres et al (2019) concluded on the important cyclic vertical support settlements on the structural response of cross vaults. The intensity of the observed damage in the two masonry vaults here analysed are different.…”
Section: Observed Damage and Structural Assesment Of Masonry Vautlsmentioning
confidence: 99%
“…The stiffness of masonry walls is analyzed in terms of the secant stiffness, defined as the ratio of 70% of the peak load in a cycle to the associated drift displacement [5,29,45,46]. The hysteresis loops show that the secant stiffness decreases with an increase in the applied displacement.…”
Section: Stiffness and Strength Degradationmentioning
confidence: 99%
“…In order to assess the structural degradation, the stiffness K corresponding to a certain drift value was obtained as the secant stiffness at 70% of the maximum load of the cycle [20,27]. Stiffness was determined for both directions of displacement -push (-) and pull (+)-, all of which seemed to present similar degradation.…”
Section: Stiffness Degradationmentioning
confidence: 99%